PATIENT POSITIONING OUTCOMES FOR WOMEN - Power, Hilda (Operating Room Nurses Association of Canada Journal, 2002)
The purpose of this study was to determine if women undergoing gynecological surgery experienced post—operative pain, separate from surgical site pain, in the lower extremities. The study used a quasi—experimental, comparative, exploratory design. A convenience sample of 153 women, mostly day surgery patients, comprised the study sample. The women were divided into two groups; Group I consisted of women for specific procedures requiring the lithotomy position and Group II consisted of women for specific procedures requiring the supine position. Descriptive statistics were used in the data analysis of the positioning guidelines and pain scale scores. Pearson’s Moment Correlations were used to determine relationships among the variables and T-test analysis was used to compare the differences between the two groups.